Beyond timber: balancing demands for tree resources between concessionaires and villagers - Tieguhong, J.C.; Snook, Laura K.; Taedoumg, H.E.; Maukonen, P.; Tchatat, M.; Loo, J.; Tchingsabe, O.; Noutcheu, R.; Iponga, D.M.; Kahindo, J.M.; Muvatsi, P.; Yobo, C.M.; et al. (2017)
Extensive areas of the Congo Basin forest are allocated to timber concessionaires. These forests also harbour and support village populations, including indigenous Baka people, who depend on forest foods obtained directly from trees (fruits, oils and caterpillars). Most food-producing tree species are harvested by concessionaires for timber. We documented the availability and abundance of three food tree species around four villages and in two neighboring timber concessions in Cameroon. Data was used to determine the importance of timber concessions as sources of food for local people to provide a foundation for governance arrangements that consider local needs for foods from timber trees. Discussions with concessionaires revealed that some of them have voluntarily refrained from extracting timber species of interest to villagers for their nontimber products. This is either to avoid conflict with villagers, or because regulations have been promulgated to safeguard these resources. The interplay between internal village dynamics, regulations and their implementation by forest guards, and the actions of timber concessions create a complex arena for addressing rights to forest resources. This paper provides information on the accessibility and availability of multiple use timber species as a foundation for negotiations and governance arrangements between concessionaires and local communities.